On the taxonomic status of the enigmatic Phycolepidoziaceae (Marchantiophyta: Jungermanniales) with description of a new species, Phycolepidozia indica. Issue 3 (2nd June 2014) - Gradstein, S. Robbert; Laenen, Benjamin; Frahm, Jan-Peter; Schwarz, Uwe; Crandall-Stotler, Barbara J.; Engel, John J.; Von Konrat, Matthew; Stotler, Raymond E.; Shaw, Blanka; Shaw, A. Jonathan
Abstract: The monospecific Phycolepidoziaceae with the single neotropical species Phycolepidozia exigua is a highly specialized leafy liverwort without vegetative leaves. The extreme reduction of morphological and anatomical characters of Phycolepidozia has caused uncertainties as to the systematic position of the genus and family. In 2012, a second species of Phycolepidozia was detected in the Western Ghats, South India. The Indian plant differs from P. exigua in several respects and is described here as P. (subg. Metaphycolepidozia ) indica Gradst., J.‐P.Frahm & U.Schwarz. Differences include the massive stem of P. indica, the larger perianth with a crenate, 3‐lobed mouth, and the epidermis of the capsule wall made up of non‐tiered cells with nodular thickenings on both longitudinal and transverse walls. A phylogenetic analysis using four different chloroplast regions ( psbA, psbT, rps4, rbcL ) of P. indica and putatively related groups shows that Phycolepidozia is nested within the leafy liverwort family Cephaloziellaceae. Consequently, Phycolepidoziaceae is placed in the synonymy of Cephaloziellaceae. The discovery of P. indica adds a further example to the list of amphi‐Pacific tropical disjunctions in bryophytes.